ANALISIS PERBANDINGAN ANTARA ECONOMIC VALUE ADDED (EVA) DENGAN RETURN ON ASSET (ROA) DALAM MENILAI KINERJA KEUANGAN PERBANKAN TAHUN 2014-2017 PADA BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Deni Sunaryo (LPPM UNIBI, 2019)
This study aims to assess the financial performance of bank by using the methodof Economic Value Added (EVA) and Return On Assets (ROA). The method used in thisstudy is comparative method / comparison. Scope of this research is BUMN bank listedon Indonesia Stock Exchange.Based on the research result of sig-2 tailed 0,271. This means more than asignificant requirement of 0,005 which means there can difference between financialperformance by using the method of EVA and ROA. From the results of EVA’S and ROAcalculation shows that all banks have a positive average.